2018
DOI: 10.1111/imm.12957
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 signalling regulates antibody response to adenoviral vector‐based vaccines by imprinting germinal centre quality

Abstract: Adenoviral vectors (AdV) are considered promising candidates for vaccine applications. A prominent group of Toll-like receptors (TLRs) participate in the adenovirus-induced adaptive immune response, yet there is little information regarding the role of TLR4 in AdV-induced immune responses in recent literature. We investigated the function of TLR4 in both adaptive and innate immune responses to an AdV-based anthrax vaccine. By immunizing wild-type and TLR4 knockout (TLR4-KO) mice, we revealed the requirement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…When TLRs recognize relevant molecules, they activate downstream regulatory molecules such as NF-κB or interferon regulatory factor (IRF) to conduct immune signal transduction and induce and stimulate cells to produce effector molecules to kill foreign pathogens ( 13 ). TLR 4 is an important part of the TLRs family ( 42 , 43 ). Numerous studies found that TLR 4 recognizes peptides and activates the downstream regulatory signal pathways, such as NF-κB and MAPK, to exert immunomodulatory effects ( 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…When TLRs recognize relevant molecules, they activate downstream regulatory molecules such as NF-κB or interferon regulatory factor (IRF) to conduct immune signal transduction and induce and stimulate cells to produce effector molecules to kill foreign pathogens ( 13 ). TLR 4 is an important part of the TLRs family ( 42 , 43 ). Numerous studies found that TLR 4 recognizes peptides and activates the downstream regulatory signal pathways, such as NF-κB and MAPK, to exert immunomodulatory effects ( 44 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…The proinflammatory signal clinically manifests as typical reactions towards vaccination within the first 24 to 48 hours, which include fever, chills, and headache. These acute reactions are likely induced by proteins in the vaccine, especially the non-assembled hexon proteins (see above), which can bind to innate immune cell receptors [39] , inducing inflammation.…”
Section: Pf4 As a Label Of Pathogensmentioning
confidence: 99%
“…In contrast, interferon signaling to both B cells and CD4 + T cells was required for optimal production of IgG. Another study examining the impact of TLR4 deficiency on Ad5‐induced humoral immune responses also identified impaired GC responses, lower transgene‐specific IgG titers, and impaired CD4 + T cell responses [ 116 ]. Whether this shared phenotype reflects a common pathway around impaired induction of type I interferon in the absence of TLR4 signaling was not explored.…”
Section: Adenovirus Vectorsmentioning
confidence: 99%